Gambaran Coping Stress pada Mahasiswa yang sedang Menyelesaikan Skripsi - Sugiarti Sugiarti; Rismar Julia Utami; Al Ikhlas; Devin Mahendika; Antonius Rino Vanchapo; M Aufa Muis (Journal on Education, 2024)
Thesis is a type of scientific writing written by students and one of the requirements to achieve a bachelor‟s degree. Difficulty in working on a thesis makes the state and mind decrease, this condition is called stress. To cope with stress in completing the student‟s thesis doing coping. This study conducted to determine the description of the coping stress in completing their thesis and to describe the students' coping by gender. The method that used in this research is a quantitative research using the descriptive method. The subject of this research was 70 students in completing their thesis. Total sampling is used as a technique of selecting the participant in this research. Google Form Questionnaire was used to collect the data. The collected data were analyzed by using descriptive statistics. The data analyses revealed that 41.4% are in the medium category, 18.6% are in the high category, and 8.6% are in the very high category. Means that most students in completing their thesis have good stress coping. Besides, there are no significant differences between male and female students.